THE VALUE OF THE HERPES VIRUS TYPE 6 IN THE GENESIS OF SEIZURES IN CHILDREN - L. V. Vashura; M. S. Savenkova; M. P. Savenkov; M. Yu. Kalugina; N. V. Karazhas; T. N. Rybalkina; I. R. Samsonovich (LLC "Diagnostics and Vaccines", 2015)
The value of human herpes virus type 6 (HHV-6) in the structure of seizures in 114 children in three groups of patients: with neuroinfections, with epilepsy and febrile convulsions was studied. Determination of HHV-6 by polymerase chain reaction in the acute period of the disease is a reliable sign (p < 0.001), and most often diagnosed in children in the group with febrile seizures (53.8%). Recovery in children with seizures caused by HHV-6, was observed only in 28% of cases,38.8% of patients in the outcome of the disease expand the epilepsy.